U-Pb ages of the Nardanda Pegmatite of the Kathmandu Crystalline Nappe and augen gneisses of the Gosaikund Crystalline Nappe, Central Nepal Himalaya - Rai, Santa Man; Upreti, Bishal Nath; Parrish, Randy; Copeland, Peter; Fort, Patrick Le (Journal of Nepal Geological Society, 2011)
Available with full text.